Green finance in renewable energy: Comparative analysis of successful country cases - Soto, Alejandra Ornelas (ADA University, 2020)
Green Finance is a new topic emerged from the need of finding funds to develop projects aimed at protecting the environment for a sustainable future and to keep global warming under 2ºC above preindustrial levels. To reach that goal, the United Nations estimates an investment of $1 trillion dollars per year by 2030, however, the world barely reached USD$272.9 billion in 2018. This research studies the green instruments applied by 5 countries with the greatest renewable capacity investment in the last 10 years, according to a ranking developed by Bloomberg. Through the case study of fiscal and monetary policies of each country in the period from 2007 to 2018, and the correlation analysis of greenhouse gas emission, renewable energy consumption, fossil fuel consumption, carbon emission and renewable investment capacity, the author will search whether the funds invested in renewable energies have helped to reduce greenhouse gas and carbon emissions or not. Results show that, in order to reduce greenhouse gas and carbon emissions, it is not enough to only invest in renewable energies and increase renewable energy consumption, but to strengthen the labeling systems and green financial instruments guidelines in order to allocate the funds properly. Despite that China and Germany occupied the first and fourth places of Bloomberg’s ranking, their poor definition of “green” investment allowed them to allocate funds in “clean coal” and biomass, respectively. As a consequence, those two countries show a rising pattern in their data of oil and coal consumption and carbon emission as they increase their investment in renewable energies.
Keywords: Public and International Affairs; Green finance.; Climate change.; Global warming.